Efficacy and safety of SQ house dust mite sublingual immunotherapy‐tablet in Japanese children. Issue 12 (10th October 2018) - Masuyama, Keisuke; Okamoto, Yoshitaka; Okamiya, Kazuhiro; Azuma, Ryuji; Fujinami, Toshiaki; Riis, Bente; Ohashi‐Doi, Katsuyo; Natsui, Kensuke; Imai, Toru; Okubo, Kimihiro
Abstract: Background: The SQ house dust mite (HDM) sublingual immunotherapy (SLIT)‐tablet (TO‐203, Torii, Japan/ALK, Denmark) treatment has been effective against respiratory allergic diseases in patients aged ≥12 years during European, Japanese, and North American trials. This trial was conducted to investigate the efficacy and safety of this treatment in Japanese children (5‐17 years) with moderate‐to‐severe HDM allergic rhinitis (AR). Methods: In this randomized, double‐blind, placebo‐controlled trial, 458 Japanese children were randomly assigned to a daily SQ HDM SLIT‐tablet [10 000 Japanese Allergy Unit (JAU), equivalent to 6 SQ‐HDM in Europe and the US] or placebo (1:1) treatment for 1 year. Inclusion required an AR symptom score of ≥7 on at least 7 days during a 14‐day run‐in period while symptomatic treatment was withdrawn. The primary endpoint was the total combined rhinitis score (TCRS) comprising AR symptom and medication scores during the last 8 weeks of the treatment period. Results: The analysis of primary endpoint demonstrated statistically significant absolute reduction in TCRS of 1.22 with a relative difference of 23% (95% confidence interval, 14% to 31%) in the 10 000 JAU compared with placebo. Predefined stratified analyses revealed the same degree of efficacy of 1.11 ( P  =   0.002), 21% (8% to 32%) and 1.36 ( P  =   0.001), 26% (11% to 38%), respectively, in pediatric (5‐11 years) and adolescent subjects (12‐17 years). The treatment was well tolerated by both pediatric and adolescent subjects. Conclusion: This trial, for the first time, demonstrated the efficacy and safety of the HDM SLIT‐tablet in pediatric patients with moderate‐to‐severe HDM AR (JapicCTI‐152953). Abstract : This randomized, double‐blind, placebo‐controlled phase III clinical trial demonstrated the efficacy and favorable safety profile of the SQ HDM SLIT‐tablet in Japanese pediatric and adolescent patients with moderate‐to‐severe HDM‐induced AR. The 10 000 JAU group showed statistically significant improvement compared with placebo group in primary endpoint, TCRS during the last 8 weeks of the treatment period. No relevant difference in the efficacy and safety profile was observed between pediatric and adolescent subjects. HDM, house dust mite; SLIT, sublingual immunotherapy; AR, allergic rhinitis; JAU, Japanese allergy unit; TCRS, total combined rhinitis score.